MHR Was Associated with Hyperuricemia Risk in Patients with Type 2 Diabetes Mellitus: The Mediating Effect of Body Mass Index - Huang B; Li X; Zhang XX; Li SW; Wang M; Chen Q; Cao YD; Cui JQ (Diabetes, Metabolic Syndrome and Obesity)
Bo Huang,1,* Xin Li,1,* Xin-Xin Zhang,2 Shi-Wei Li,1 Meng Wang,1 Qing Chen,3 Yi-Dan Cao,3 Jing-Qiu Cui1 1Department of Endocrinology and Metabolism, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China; 2Department of Nephrology, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China; 3Department of Epidemiology and Statistics, School of Public Health, Tianjin Medical University, Tianjin, 300070, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing-Qiu Cui, Department of Endocrinology and Metabolism, Tianjin Medical University General Hospital, An Shan Dao 154, Tianjin, 300052, People’s Republic of China, Tel +86-13920765604, Email cuijingqiu@tmu.edu.cnBackground: The monocyte-to-high-density lipoprotein cholesterol ratio (MHR) reflects systemic inflammation, combining the pro-inflammatory role of monocytes with the anti-atherogenic and anti-inflammatory properties of HDL-cholesterol. Prior studies have established MHR as an independent predictor of hyperuricemia (HUA) prevalence. Emerging evidence further identifies MHR as a potential biomarker for early type 2 diabetes mellitus (T2DM) screening, likely mediated through its association with insulin resistance. Therefore, our study specifically investigates the relationship between MHR and HUA in a T2DM population.Methods: This cross-sectional study enrolled 1,261 T2DM patients. Logistic regression assessed associations between MHR and HUA. Mediation analysis evaluated body mass index (BMI) as a mediator. Restricted cubic spline (RCS) analysis examined nonlinear relationships. Receiver operating characteristic (ROC) curves compared predictive performance.Results: Elevated MHR (adjusted OR = 2.040, 95% CI: 1.023 to 4.071, p < 0.05) was independently associated with HUA risk. BMI mediated 18.59% of the associations for MHR, respectively. RCS analysis revealed nonlinear patterns, with HUA risk increasing notably when MHR > 0.47. In ROC analysis, MHR demonstrated significant predictive ability for HUA, with an area under the curve (AUC) of 0.62.Conclusion: Higher MHR was significantly associated with HUA risk in T2DM patients, with BMI serving as a key mediator. These markers may aid in early identification of patients at risk and underscore the importance of weight and inflammation control in HUA prevention.Keywords: hyperuricemia, MHR, body mass index, mediation effect analysis, T2DM